Ultrafast dynamics of ionic liquids in colloidal dispersion. Issue 48 (30th November 2017) - Ren, Zhe; Kelly, Jordan; Gunathilaka, C. Prasad; Brinzer, Thomas; Dutta, Samrat; Johnson, Clinton A.; Mitra, Sunayana; Garrett-Roe, Sean
Abstract : The dynamics of [BMIM][SCN] microemulsions depend on the surfactant, size, and the oil-phase. Abstract : Ionic liquid (IL)–surfactant complexes have significance both in applications and fundamental research, but their underlying dynamics are not well understood. We apply polarization-controlled two-dimensional infrared spectroscopy (2D-IR) to study the dynamics of [BMIM][SCN]/surfactant/solvent model systems. We examine the effect of the choice of surfactants and solvent, and the IL-to-surfactant ratio ( W -value), with a detailed analysis of the orientation and structural dynamics of each system. Different surfactants create very different environments for the entrapped ILs, ranging from a semi-static micro-environment to a fluxional environment that evolves even faster than the bulk IL. The oil-phase also clearly affects the microscopic dynamics. The anisotropy decay for entrapped ILs completes within 10 ps, which is similar to free thiocyanate ion in water, while a significant reorientation-induced spectral diffusion (RISD) effect is observed. The entrapped ionic liquid are highly dynamic for all W -values, and no core–shell structure is observed. We hypothesize that, instead of an ionic liquid-reverse micelle (IL-RM), the microscopic structure of this system is small colloidal dispersions or pairs of IL and surfactants. A detailed analysis of the polarization-controlled 2D-IR spectra of AOT system reveals a potential ion-exchange mechanism.